Zakat Produktif dalam Perspektif Syariah dan Peraturan di Indonesia - Efri Syamsul Bahri; Prasetio Ariwibowo; Hamzah Robbani (LITERATUS, 2020)
This paper describes the review of productive zakat in sharia and regulatory perspectives. This research uses library research methods by reviewing and collecting the results of previous studies that are in line with the theme of this study. The results of this study indicate that productive zakat in sharia perspective is allowed to improve the economic life of the mustahiq and meet the needs in worshiping Allah SWT. While productive zakat from a regulatory perspective in Indonesia is at the macro, meso, and micro levels.The authenticity of this study is permissible and productive zakat. A new aspect of this research is conducting a study with two discussions namely the sharia perspective and regulatory perspective in Indonesia.